Rice price volatility and transmission: implications for food security in Ghana - Edward E. Onumah; Prince Addey Owusu; Akwasi Mensah-Bonsu; Henry Acquah Degraft (Cogent Economics & Finance, 2022)
This paper examines price volatility and transmission of rice markets in Ghana and draws implications for food security. Using monthly rice price data from 2013 to 2019, the paper uses the Autoregressive Distributed Lag (ARDL) with an Error Correction Model (ECM) to ascertain the availability and accessibility of rice, whilst the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model is considered to measure the stability of the commodity. The paper finds evidence of cointegration between the World and Ghana's rice market. Findings confirm cointegration in Ghana's regional markets for both imported and domestically produced rice. This ensures stable long-run relationship, allowing trade flows that guarantees rice availability. The corrections in short-run deviations of price ensure continuous accessibility of rice in the country. Estimates from the volatility model suggest high fluctuation in prices, implying that stability in the prices of rice is an issue across all regional markets. The paper recommends efforts in increasing domestic production to enhance availability and accessibility of rice. Stakeholders along the rice value chain should be encouraged to invest in competitive rice production. Government should leverage rice prices with giant import countries to reduce the cost of importation for stable price on the market.
Keywords: 330; Price transmission; market integration; volatility; food security